MYC protein expression is an important prognostic factor in acute myeloid leukemia. Issue 1 (2nd January 2019) - Ohanian, Maro; Rozovski, Uri; Kanagal-Shamanna, Rashmi; Abruzzo, Lynne V.; Loghavi, Sanam; Kadia, Tapan; Futreal, Andrew; Bhalla, Kapil; Zuo, Zhuang; Huh, Yang O.; Post, Sean M.; Ruvolo, Peter; et al.
Abstract: As new drugs targeting MYC show clinical activity in acute myeloid leukemia (AML), understanding MYC expression in AML is of critical importance. We assessed MYC protein expression by immunohistochemistry in bone marrow of patients with untreated AML ( n = 265). Overall, 90% of patients demonstrated MYC overexpression and MYC immunopositivity ≤6% was associated with superior complete remission (CR) duration of 23 months versus 12 months for MYC immunopositivity >6% ( p = .028). Among 241 patients at higher risk for relapse, including those ≥55 years of age and patients with intermediate- and high-risk AML, MYC immunopositivity ≤6% conferred significantly superior median overall survival (OS) (24 versus 13 months; p = .042), event-free survival (EFS) (14 versus 6 months; p = .048), and relapse-free survival (RFS) (25 versus 12 months; p = .024). The prognostic impact of MYC-immunopositivity was retained on multivariate analysis of OS, EFS, and RFS. We conclude that MYC immunopositivity is an important prognostic factor in patients with untreated AML, particularly those at higher risk for relapse.